Haemodynamic parameters and cognitive function during modeled acute volume loss - Tuboly, G; Rudas, L; Csillik, A; Nagy, A; Benedek, K; Benedek, György; Braunitzer, G (Acta physiologica Hungarica, 2012)
The purpose of the present study was to find a noninvasive way of detecting even smaller volume loss which is easier to carry out and possibly more precise than the currently used (mostly sphygmomanometer-based) methods. Haemodynamic and EEG measurements were carried out in simulated volume loss, involving blood donation and orthostatic challenges to assess adaptive responses and cognitive performance. Cognitive performance was assessed in an oddball task and changes of the evoked potential P300 were analyzed. Both haemodynamic and cognitive parameters were recorded in 'pre-donation' and 'post-donation' conditions for purposes of comparison. Cognitive performance (as reflected by P300 changes) was found to be a poor marker of volume loss. Difference between the two conditions in none of the parameters reached the level of statistical significance (defined as p < 0.05) RR mean, baroreceptor sensitivity and pulse pressure were rather sensitive to the relatively mild volume loss (p < 0.01 between pre- and post-conditions). Our study indicates that traditional sphygmomanometer based values can safely be replaced by values yielded by finger plethysmography, combined with brief orthostatic challenges and that P300 as a cognitive marker cannot be used to assess volume loss.